ISLAMIC PHILANTHROPHY FOR INCLUSIVE EDUCATION AND ITS IMPACT ON SUSTAINABLE DEVELOPMENT - Shibgotulloh, Ilman Faqih; Farid Septian (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Since 2020 BAZNAS has implemented a Special Partnership Scholarship program with institutions that have expertise in Education for Disabilities, 3T Regions and Indigenous Communities as BAZNAS's sanding partners to improve the quality of human resources through education. This study aims to analyze the special partnership program model to improve the quality of education for groups with disabilities, 3T Regions and Indigenous Communities. This research uses a quantitative descriptive method with a purposive sample type consisting of 18 partner institutions since 2020-2022 and institutional beneficiaries consisting of a sample of 151 beneficiaries. and spread across Yogyakarta, East Kalimantan, West Sulawesi, Banten, Maluku, East Nusa Tenggara, West Nusa Tenggara, Aceh, West Sumatra, Jambi, East Java, Central Java and South Sulawesi. data collection was carried out by distributing interview instruments, documentation, and observation. Meanwhile, the program impact evaluation used the CIPP model, which is an education program evaluation with 4 (four) approaches (Context, Input, Process, Product). The results showed that the effectiveness score or impact of the Scholarship Program for special disabilities, 3T areas and indigenous communities had a significant impact on partner institutions. The results showed that the effectiveness score or impact of the Scholarship Program for special disabilities, 3T areas and indigenous communities had a significant impact on partner institutions.